Biodegradable alloy, preparation method and preparation device thereof

By adding trace elements such as Ga, Cr, V to the biodegradable alloy, and using high-energy ultrasonic treatment and homogenization treatment technology, the alloy's shortcomings in corrosion resistance and high ductility are solved, and the mechanical properties and corrosion resistance of the alloy are improved, and it is suitable for medical implantable materials.

CN119776700APending Publication Date: 2025-04-08广东海洋大学阳江研究院
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510096174.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-22
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

Existing biodegradable alloys cannot meet the needs of corrosion resistance and high ductility at the same time, resulting in limited applications in the medical device field.

Method used

By adding trace elements such as Ga, Cr, V, etc., a biodegradable alloy containing V, Cr, Ga, Cu, Ag, Mg and Zn elements is prepared, and high-energy ultrasonic treatment and homogenization treatment technology are used to improve the mechanical properties and corrosion resistance of the alloy.

Benefits of technology

The solid solution strengthening and precipitation strengthening of the alloy is achieved, and its mechanical properties, tensile strength, yield strength and elongation are improved. At the same time, it has good corrosion resistance and is suitable for medically degradable implantable materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119776700A_ABST
    Figure CN119776700A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of biodegradable materials, in particular to a biodegradable alloy, a preparation method and a preparation device thereof, and the alloy comprises V, Cr, Ga, Cu, Ag, Mg and Zn elements. Wherein the mass fraction of V is 0.1%-0.6%, the mass fraction of Cr is 0.1%-0.4%, the mass fraction of Ga is 0.6%-2.36%, the mass fraction of Cu is 0.1%-2.75%, the mass fraction of Ag is 1.0%-4.0%, the mass fraction of Mg is 1.7%-3.7%, and the balance is Zn. Compared with the prior art, the Zn-based alloy can generate solution strengthening and precipitation strengthening effects by adding Ga, Cr, V and other trace elements, the mechanical property of the Zn-based alloy can be improved, the Zn-based alloy has good corrosion resistance, tensile strength, yield strength and ductility, high-energy ultrasonic melt treatment and standing heat preservation are adopted in the method, uniform alloy components can be obtained, and the method is suitable for large-scale production. Through homogenization treatment, a strengthening phase is uniformly distributed, the mechanical property is stable, and the device can be used as a medical degradable implant material, can integrate vacuum, ultrasonic and air intake, and is convenient to use.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of biodegradable materials. Background Art

[0002] In order to achieve fully controllable biodegradation in the body while maintaining good biocompatibility and the required mechanical properties, magnesium-based, iron-based and zinc-based biodegradable metal materials have become a hot topic in the research of medical implant metal materials. The excessive degradation rate of magnesium-based alloys will seriously affect the mechanical integrity of the implant, while the degradation rate of iron-based alloys is too slow, but the corrosion products will remain in the body for a long time and cause complications. In comparison, zinc alloys have been proven to have a suitable corrosion rate and good mechanical integrity, and have great application prospects in the field of medical devices. Elemental zinc cannot meet the required mechanical properties when used as a ureteral implant stent material. Zinc-based implant materials will release Zn during the degradation process. 2+ At low concentrations, it can improve cell viability, while at high concentrations, on the contrary, it will produce cytotoxicity and delay the bone integration between the implant and the new bone. The concentration of zinc ion degradation products is directly related to the corrosion rate. The existing technology improves the corrosion resistance of zinc alloys by alloying zinc with non-toxic elements or modifying the surface of zinc alloy implants to control the corrosion rate. Therefore, Zn-Mg based binary alloy materials are prepared by adding Mg and other elements to Zn as the matrix, which can refine the grain structure and improve the mechanical properties. However, when the magnesium content increases to several weight percentages, the strength of most studied Zn-Mg alloys can be slightly improved, but their ductility decreases rapidly. Summary of the invention

[0003] In order to overcome the technical problem in the prior art that biodegradable alloys cannot simultaneously meet the requirements of corrosion resistance and high ductility, the present invention provides a biodegradable alloy, a preparation method and a preparation device thereof.

[0004] The technical solution adopted by the present invention to achieve the above-mentioned purpose is: a biodegradable alloy, comprising V, Cr, Ga, Cu, Ag, Mg and Zn elements, wherein the mass fraction of V is 0.1%-0.6%, the mass fraction of Cr is 0.1%-0.4%, the mass fraction of Ga is 0.6%-2.36%, the mass fraction of Cu is 0.1%-2.75%, the mass fraction of Ag is 1.0%-4.0%, the mass fraction of Mg is 1.7%-3.7%, and the balance is Zn.

[0005] A method for preparing a biodegradable alloy comprises the following steps:

[0006] S1: Weigh metal V, metal Cr, metal Ga, metal Zn, metal Ag, Zn-50wt% Mg alloy, and Zn-38wt% Cu alloy; wherein the mass of metal V accounts for 0.1%-0.6% of the total raw material mass, the mass of metal Cr accounts for 0.1%-0.4% of the total raw material mass, the mass of metal Ga accounts for 0.6%-2.36% of the total raw material mass, the mass of Cu element contained in Zn-38wt% Cu alloy accounts for 0.1%-2.75% of the total raw material mass, the mass of metal Ag accounts for 1.0%-4.0% of the total raw material mass, the mass of Mg element contained in Zn-50wt% Mg alloy accounts for 1.7%-3.7% of the total raw material mass, and the rest is metal Zn;

[0007] S2: adding all the metal Zn and metal Ag into a high-purity alumina crucible in a vacuum induction melting furnace, and filling the vacuum induction melting furnace with argon as a protective gas, heating to the melting temperature to completely melt the metal Zn and metal Ag, and keeping them warm at the melting temperature;

[0008] S3: continue to add metal V, metal Cr, metal Ga, Zn-Mg alloy, and Zn-Cu alloy into the high-purity alumina crucible, stir after completely melting to obtain a melt, cool the melt to a pouring temperature, and then keep it warm at the pouring temperature;

[0009] S4: using ultrasonic equipment to perform high-energy ultrasonic treatment on the melt in the high-purity alumina crucible;

[0010] S5: pouring the treated melt to obtain an ingot, removing the top and bottom of the ingot to obtain an alloy billet;

[0011] S6: The alloy billet is subjected to homogenization treatment and conventional hot extrusion to obtain a biodegradable alloy.

[0012] Preferably, in step S2, the flow rate of the argon gas is 15-20 L / min, the melting temperature is 550-650° C., and the insulation time is 30-40 min.

[0013] Preferably, in step S2, the stirring speed is 50-80 r / min, the stirring time is 20-30 min, the pouring temperature is 520-620° C., and the insulation time is 30-60 min.

[0014] Preferably, in the high-energy ultrasonic treatment process described in step S4, the ultrasonic frequency is 19 KHz, and the high-energy ultrasonic treatment time is 45-60 seconds.

[0015] Preferably, the temperature of the homogenization treatment in step S6 is 250-350° C., the time of the homogenization treatment is 10-15 hours, the temperature of the conventional hot extrusion is 250-450° C., the extrusion speed is 0.2-2.0 mm / min, and the extrusion ratio is 25-95:1.

[0016] A preparation device for a biodegradable alloy comprises a vacuum induction melting furnace 1, a vacuum pump is provided on one side of the vacuum induction melting furnace 1, the vacuum pump is communicated with the interior of the vacuum induction melting furnace, a high-purity alumina crucible is provided in the vacuum induction melting furnace, an ultrasonic generator is provided above the vacuum induction melting furnace, an ultrasonic rod is connected to the lower end of the ultrasonic generator, the end of the ultrasonic rod passes through the vacuum induction melting furnace and extends into the high-purity alumina crucible, an air inlet pipe is provided on the vacuum induction melting furnace, an air inlet valve is provided on the air inlet pipe, an outlet of the air inlet pipe is communicated with the interior of the vacuum induction melting furnace, a feeding chamber is provided on the vacuum induction melting furnace, a feeding pipe is provided below the feeding chamber, the upper end of the feeding pipe is communicated with the feeding chamber, the lower end of the feeding pipe is communicated with the interior of the vacuum induction melting furnace, and the discharge end of the feeding pipe corresponds to the high-purity alumina crucible.

[0017] Preferably, the vacuum induction melting furnace is provided with a pressure gauge and a thermometer connected to the interior thereof.

[0018] Compared with the prior art, the present invention can make Zn-based alloy produce solid solution strengthening and precipitation strengthening effects by adding trace elements such as Ga, Cr, V, etc., can improve its mechanical properties, and has good corrosion resistance, tensile strength, yield strength and elongation. The method adopts high-energy ultrasonic treatment of the melt and static insulation to obtain uniform alloy composition. Through homogenization treatment, the strengthening phase is evenly distributed and the mechanical properties are stable. It can be used as a medical degradable implant material. The device can integrate vacuum, ultrasound and air intake, and is easy to use. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 It is a schematic diagram of a preparation device of a biodegradable alloy of the present invention.

[0020] Figure 2 1 is a graph showing the tensile strength, elongation and yield strength test results of Example 1, Example 2 and Example 3 of the present invention.

[0021] In the figure: 1: vacuum induction melting furnace; 2: high-purity alumina crucible; 3: vacuum pump; 4: ultrasonic generator; 5: ultrasonic rod; 6: air inlet pipe; 7: feed chamber; 8: feed pipe; 9: pressure gauge; 10: thermometer. DETAILED DESCRIPTION

[0022] The specific implementation methods of the present invention are as follows:

[0023] Embodiment 1:

[0024] A biodegradable alloy

[0025] It includes V, Cr, Ga, Cu, Ag, Mg and Zn elements, wherein the mass fraction of V is 0.15%, the mass fraction of Cr is 0.1%, the mass fraction of Ga is 0.6%, the mass fraction of Cu is 0.1%, the mass fraction of Ag is 4.0%, the mass fraction of Mg is 3.7%, and the balance is Zn.

[0026] A method for preparing a biodegradable alloy comprises the following steps:

[0027] S1: Weigh metal V, metal Cr, metal Ga, metal Zn, metal Ag, Zn-50wt% Mg alloy, and Zn-38wt% Cu alloy; wherein the mass of metal V accounts for 0.15% of the total raw material mass, the mass of metal Cr accounts for 0.1% of the total raw material mass, the mass of metal Ga accounts for 0.6% of the total raw material mass, the mass of Cu element contained in Zn-38wt% Cu alloy accounts for 0.1% of the total raw material mass, the mass of metal Ag accounts for 4.0% of the total raw material mass, the mass of Mg element contained in Zn-50wt% Mg alloy accounts for 3.7% of the total raw material mass, and the rest is metal Zn;

[0028] S2: Add all the metal Zn and metal Ag into a high-purity alumina crucible in a vacuum induction melting furnace, and fill the vacuum induction melting furnace with argon at a flow rate of 15L / min as a protective gas, heat to the melting temperature to completely melt the metal Zn and metal Ag, and keep them warm at the melting temperature, the melting temperature is 550°C, and the holding time is 30min;

[0029] S3: continue to add metal V, metal Cr, metal Ga, Zn-Mg alloy, and Zn-Cu alloy into the high-purity alumina crucible, stir after completely melting to obtain a melt, cool the melt to a pouring temperature, and then keep it warm at a pouring temperature of 520°C, with a stirring speed of 50 r / min, a stirring time of 20 min, and a holding time of 30 min;

[0030] S4: using ultrasonic equipment to perform high-energy ultrasonic treatment on the melt in the high-purity alumina crucible, the ultrasonic frequency is 19KHz, and the high-energy ultrasonic treatment time is 45s;

[0031] S5: pouring the treated melt to obtain an ingot, removing 5 cm from the top and 5 cm from the bottom of the ingot to obtain an alloy billet;

[0032] S6: subjecting the alloy billet to homogenization treatment and conventional hot extrusion, wherein the homogenization treatment temperature is 250° C., the homogenization treatment time is 10 hours, the conventional hot extrusion temperature is 250° C., the extrusion speed is 0.2 mm / min, and the extrusion ratio is 25:1, to obtain a biodegradable alloy.

[0033] Embodiment 2:

[0034] A biodegradable alloy

[0035] It includes V, Cr, Ga, Cu, Ag, Mg and Zn elements, wherein the mass fraction of V is 0.35%, the mass fraction of Cr is 0.2%, the mass fraction of Ga is 1.15%, the mass fraction of Cu is 2.75%, the mass fraction of Ag is 3.0%, the mass fraction of Mg is 1.7%, and the balance is Zn.

[0036] A method for preparing a biodegradable alloy comprises the following steps:

[0037] S1: Weigh metal V, metal Cr, metal Ga, metal Zn, metal Ag, Zn-50wt% Mg alloy, and Zn-38wt% Cu alloy; wherein the mass of metal V accounts for 0.35% of the total raw material mass, the mass of metal Cr accounts for 0.2% of the total raw material mass, the mass of metal Ga accounts for 1.15% of the total raw material mass, the mass of Cu element contained in Zn-38wt% Cu alloy accounts for 2.75% of the total raw material mass, the mass of metal Ag accounts for 3.0% of the total raw material mass, the mass of Mg element contained in Zn-50wt% Mg alloy accounts for 1.7% of the total raw material mass, and the rest is metal Zn;

[0038] S2: Add all the metal Zn and metal Ag into a high-purity alumina crucible in a vacuum induction melting furnace, and fill the vacuum induction melting furnace with argon at a flow rate of 17.5 L / min as a protective gas, heat to the melting temperature to completely melt the metal Zn and metal Ag, and keep them warm at the melting temperature, the melting temperature is 600°C, and the holding time is 35 minutes;

[0039] S3: continue to add metal V, metal Cr, metal Ga, Zn-Mg alloy, and Zn-Cu alloy into the high-purity alumina crucible, stir after completely melting to obtain a melt, cool the melt to the pouring temperature, and then keep it at the pouring temperature of 570°C, with a stirring speed of 65r / min, a stirring time of 25min, and a holding time of 45min;

[0040] S4: using ultrasonic equipment to perform high-energy ultrasonic treatment on the melt in the high-purity alumina crucible, the ultrasonic frequency is 19KHz, and the high-energy ultrasonic treatment time is 55s;

[0041] S5: pouring the treated melt to obtain an ingot, removing 5 cm from the top and 5 cm from the bottom to obtain an alloy billet;

[0042] S6: subjecting the alloy billet to homogenization treatment and conventional hot extrusion, the homogenization treatment temperature is 300° C., the homogenization treatment time is 12.5 hours, the conventional hot extrusion temperature is 350° C., the extrusion speed is 1 mm / min, and the extrusion ratio is 60:1, to obtain a biodegradable alloy.

[0043] Embodiment three:

[0044] A biodegradable alloy

[0045] It includes V, Cr, Ga, Cu, Ag, Mg and Zn elements, wherein the mass fraction of V is 0.4%, the mass fraction of Cr is 0.3%, the mass fraction of Ga is 2%, the mass fraction of Cu is 2%, the mass fraction of Ag is 2%, the mass fraction of Mg is 2%, and the balance is Zn.

[0046] A method for preparing a biodegradable alloy comprises the following steps:

[0047] S1: Weigh metal V, metal Cr, metal Ga, metal Zn, metal Ag, Zn-50wt% Mg alloy, and Zn-38wt% Cu alloy; wherein the mass of metal V accounts for 0.4% of the total raw material mass, the mass of metal Cr accounts for 0.3% of the total raw material mass, the mass of metal Ga accounts for 2% of the total raw material mass, the mass of Cu element contained in Zn-38wt% Cu alloy accounts for 2% of the total raw material mass, the mass of metal Ag accounts for 2% of the total raw material mass, the mass of Mg element contained in Zn-50wt% Mg alloy accounts for 2% of the total raw material mass, and the rest is metal Zn;

[0048] S2: Add all the metal Zn and metal Ag into a high-purity alumina crucible in a vacuum induction melting furnace, and fill the vacuum induction melting furnace with argon at a flow rate of 20L / min as a protective gas, heat to the melting temperature to completely melt the metal Zn and metal Ag, and keep them warm at the melting temperature, the melting temperature is 650°C, and the holding time is 40min;

[0049] S3: continue to add metal V, metal Cr, metal Ga, Zn-Mg alloy, and Zn-Cu alloy into the high-purity alumina crucible, stir after completely melting to obtain a melt, cool the melt to the pouring temperature, and then keep it warm at the pouring temperature of 620°C, with a stirring speed of 80 r / min, a stirring time of 30 min, and a holding time of 60 min;

[0050] S4: using ultrasonic equipment to perform high-energy ultrasonic treatment on the melt in the high-purity alumina crucible, the ultrasonic frequency is 19KHz, and the high-energy ultrasonic treatment time is 60s;

[0051] S5: pouring the treated melt to obtain an ingot, removing 5 cm from the top and 5 cm from the bottom of the ingot to obtain an alloy billet;

[0052] S6: subjecting the alloy billet to homogenization treatment and conventional hot extrusion, wherein the homogenization treatment temperature is 350° C., the homogenization treatment time is 15 hours, the conventional hot extrusion temperature is 450° C., the extrusion speed is 2.0 mm / min, and the extrusion ratio is 95:1, to obtain a biodegradable alloy.

[0053] Embodiment 4:

[0054] A biodegradable alloy

[0055] It includes V, Cr, Ga, Cu, Ag, Mg and Zn elements, wherein the mass fraction of V is 0.6%, the mass fraction of Cr is 0.4%, the mass fraction of Ga is 2.36%, the mass fraction of Cu is 1.1%, the mass fraction of Ag is 1%, the mass fraction of Mg is 1.6%, and the balance is Zn.

[0056] A method for preparing a biodegradable alloy comprises the following steps:

[0057] S1: Weigh metal V, metal Cr, metal Ga, metal Zn, metal Ag, Zn-50wt% Mg alloy, and Zn-38wt% Cu alloy; wherein the mass of metal V accounts for 0.6% of the total raw material mass, the mass of metal Cr accounts for 0.4% of the total raw material mass, the mass of metal Ga accounts for 2.36% of the total raw material mass, the mass of Cu element contained in Zn-38wt% Cu alloy accounts for 1.1% of the total raw material mass, the mass of metal Ag accounts for 1% of the total raw material mass, the mass of Mg element contained in Zn-50wt% Mg alloy accounts for 1.6% of the total raw material mass, and the rest is metal Zn;

[0058] S2: Add all the metal Zn and metal Ag into a high-purity alumina crucible in a vacuum induction melting furnace, and fill the vacuum induction melting furnace with argon at a flow rate of 17.5 L / min as a protective gas, heat to the melting temperature to completely melt the metal Zn and metal Ag, and keep them at the melting temperature, the melting temperature is 600°C, and the holding time is 40 minutes;

[0059] S3: continue to add metal V, metal Cr, metal Ga, Zn-Mg alloy, and Zn-Cu alloy into the high-purity alumina crucible, stir after completely melting to obtain a melt, cool the melt to the pouring temperature, and then keep it at the pouring temperature of 570°C, with a stirring speed of 65r / min, a stirring time of 25min, and a holding time of 45min;

[0060] S4: using ultrasonic equipment to perform high-energy ultrasonic treatment on the melt in the high-purity alumina crucible, the ultrasonic frequency is 19KHz, and the high-energy ultrasonic treatment time is 55s;

[0061] S5: pouring the treated melt to obtain an ingot, removing 5 cm from the top and 5 cm from the bottom of the ingot to obtain an alloy billet;

[0062] S6: subjecting the alloy billet to homogenization treatment and conventional hot extrusion, the homogenization treatment temperature is 300° C., the homogenization treatment time is 12.5 hours, the conventional hot extrusion temperature is 350° C., the extrusion speed is 1 mm / min, and the extrusion ratio is 60:1, to obtain a biodegradable alloy.

[0063] The biodegradable alloys prepared in Example 1, Example 2 and Example 3 were subjected to tensile tests. The test results are as follows: Figure 2 As shown by Figure 2 It can be seen that the tensile strength of the biodegradable alloy prepared in Example 1 is 302 MPa, the elongation is 27.1%, and the yield strength is 296 MPa. The tensile strength of the biodegradable alloy prepared in Example 2 is 340 MPa, the elongation is 33.5%, and the yield strength is 334 MPa. The tensile strength of the biodegradable alloy prepared in Example 3 is 320 MPa, the elongation is 27.7%, and the yield strength is 314 MPa. It can be seen that the results of Example 2 show that the mechanical properties of the biodegradable alloy prepared in Example 2 are the best.

[0064] The corrosion rate of the biodegradable alloys prepared in Example 1, Example 2, Example 3 and Example 4 was tested by a static weight loss experiment of immersing the alloys in a human body simulated corrosive medium SBF solution in a digital constant temperature water bath. The immersion time is 24-48h. After the immersion is completed, the sample is taken out, placed in a cleaning solution, and an ultrasonic cleaner is used to clean and remove corrosion products attached to the surface; the corrosion rate of the alloy is expressed by measuring the mass and corrosion time of the sample before and after corrosion, as well as the loss ratio of the alloy. Based on the above method, the corrosion rate of the biodegradable alloy prepared in Example 1 is 0.95±0.05mm / y, the corrosion rate of the biodegradable alloy prepared in Example 2 is 0.76±0.05mm / y, the corrosion rate of the biodegradable alloy prepared in Example 3 is 1.31±0.05mm / y, and the corrosion rate of the biodegradable alloy prepared in Example 4 is 1.52±0.05mm / y. It can be seen that the biodegradable alloy can be degraded in the human body, and the corrosion rate of the biodegradable alloy prepared in Example 2 is the best.

[0065] A preparation device for a biodegradable alloy comprises a vacuum induction melting furnace 1, a vacuum pump 3 is arranged on one side of the vacuum induction melting furnace 1, the vacuum pump 3 is communicated with the inside of the vacuum induction melting furnace 1, a high-purity alumina crucible 2 is arranged in the vacuum induction melting furnace 1, an ultrasonic generator 4 is arranged above the vacuum induction melting furnace 1, an ultrasonic rod 5 is connected to the lower end of the ultrasonic generator 4, the end of the ultrasonic rod 5 passes through the vacuum induction melting furnace 1 and extends into the high-purity alumina crucible 2, an air inlet pipe 6 is also arranged on the vacuum induction melting furnace 1, an air inlet valve 11 is arranged on the air inlet pipe 6, the outlet of the air inlet pipe 6 is communicated with the inside of the vacuum induction melting furnace 1, a feeding chamber 7 is also arranged on the vacuum induction melting furnace 1, a feeding pipe 8 is arranged below the feeding chamber 7, the upper end of the feeding pipe 8 is communicated with the feeding chamber 7, the lower end of the feeding pipe 8 is communicated with the inside of the vacuum induction melting furnace 1, and the discharge end of the feeding pipe 8 corresponds to the high-purity alumina crucible 2, and a pressure gauge 9 and a thermometer 10 communicated with the inside of the vacuum induction melting furnace 1 are provided.

[0066] Working process: add the raw materials into the high-purity alumina crucible 2 through the feed chamber 7 and the feed pipe 8, close the air inlet valve 11, start the vacuum pump 3 to evacuate the vacuum induction melting furnace 1, connect the air inlet pipe 6 to argon, open the air inlet valve 11, introduce argon into the vacuum induction melting furnace 1, start the vacuum induction melting furnace 1, melt the raw materials, and when high-energy ultrasonic treatment is required, start the ultrasonic generator 4, and the ultrasonic generator 4 acts on the high-purity alumina crucible 2 through the ultrasonic rod 5. The pressure gauge 9 is used to measure the pressure in the vacuum induction melting furnace 1, and the thermometer 10 is used to measure the temperature in the vacuum induction melting furnace 1.

[0067] The present invention is described by way of embodiments, and those skilled in the art will appreciate that various changes or equivalent substitutions may be made to these features and embodiments without departing from the spirit and scope of the present invention. In addition, under the teachings of the present invention, these features and embodiments may be modified to adapt to specific circumstances and materials without departing from the spirit and scope of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed herein, and all embodiments falling within the scope of the claims of this application belong to the protection scope of the present invention.

Claims

1. A biodegradable alloy, characterized in that: It includes V, Cr, Ga, Cu, Ag, Mg and Zn elements, wherein the mass fraction of V is 0.1%-0.6%, the mass fraction of Cr is 0.1%-0.4%, the mass fraction of Ga is 0.6%-2.36%, the mass fraction of Cu is 0.1%-2.75%, the mass fraction of Ag is 1.0%-4.0%, the mass fraction of Mg is 1.7%-3.7%, and the balance is Zn.

2. A method for preparing the biodegradable alloy according to claim 1, characterized in that: The following steps are involved: S1: Weigh metal V, metal Cr, metal Ga, metal Zn, metal Ag, Zn-50wt% Mg alloy, and Zn-38wt% Cu alloy; wherein the mass of metal V accounts for 0.1%-0.6% of the total raw material mass, the mass of metal Cr accounts for 0.1%-0.4% of the total raw material mass, the mass of metal Ga accounts for 0.6%-2.36% of the total raw material mass, the mass of Cu element contained in Zn-38wt% Cu alloy accounts for 0.1%-2.75% of the total raw material mass, the mass of metal Ag accounts for 1.0%-4.0% of the total raw material mass, the mass of Mg element contained in Zn-50wt% Mg alloy accounts for 1.7%-3.7% of the total raw material mass, and the rest is metal Zn; S2: adding all the metal Zn and metal Ag into a high-purity alumina crucible in a vacuum induction melting furnace, and filling the vacuum induction melting furnace with argon as a protective gas, heating to the melting temperature to completely melt the metal Zn and metal Ag, and keeping them warm at the melting temperature; S3: continue to add metal V, metal Cr, metal Ga, Zn-Mg alloy, and Zn-Cu alloy into the high-purity alumina crucible, stir after completely melting to obtain a melt, cool the melt to a pouring temperature, and then keep it warm at the pouring temperature; S4: using ultrasonic equipment to perform high-energy ultrasonic treatment on the melt in the high-purity alumina crucible; S5: pouring the treated melt to obtain an ingot, removing the top and bottom of the ingot to obtain an alloy billet; S6: The alloy billet is subjected to homogenization treatment and conventional hot extrusion to obtain a biodegradable alloy.

3. The method for preparing a biodegradable alloy according to claim 2, characterized in that: In step S2, the flow rate of argon gas is 15-20 L / min, the melting temperature is 550-650° C., and the insulation time is 30-40 min.

4. The method for preparing a biodegradable alloy according to claim 2, characterized in that: In step S3, the stirring speed is 50-80 r / min, the stirring time is 20-30 min, the pouring temperature is 520-620° C., and the insulation time is 30-60 min.

5. The method for preparing a biodegradable alloy according to claim 2, characterized in that: In the high-energy ultrasonic treatment process described in step S4, the ultrasonic frequency is 19 KHz, and the high-energy ultrasonic treatment time is 45-60 seconds.

6. The method for preparing a biodegradable alloy according to claim 2, characterized in that: The temperature of the homogenization treatment in step S6 is 250-350° C., the time of the homogenization treatment is 10-15 hours, the temperature of the conventional hot extrusion is 250-450° C., the extrusion speed is 0.2-2.0 mm / min, and the extrusion ratio is 25-95:

1.

7. A device for preparing a biodegradable alloy as claimed in claim 1, characterized in that: The invention comprises a vacuum induction melting furnace (1), wherein a vacuum pump (3) is provided on one side of the vacuum induction melting furnace (1), wherein the vacuum pump (3) is connected to the inside of the vacuum induction melting furnace (1), wherein a high-purity alumina crucible (2) is provided in the vacuum induction melting furnace (1), wherein an ultrasonic generator (4) is provided above the vacuum induction melting furnace (1), wherein an ultrasonic rod (5) is connected to the lower end of the ultrasonic generator (4), wherein the end of the ultrasonic rod (5) passes through the vacuum induction melting furnace (1) and extends into the high-purity alumina crucible (2), wherein a vacuum The induction melting furnace (1) is also provided with an air inlet pipe (6), the air inlet pipe (6) is provided with an air inlet valve (11), the outlet of the air inlet pipe (6) is connected to the interior of the vacuum induction melting furnace (1), the vacuum induction melting furnace (1) is also provided with a feed chamber (7), a feed pipe (8) is provided below the feed chamber (7), the upper end of the feed pipe (8) is connected to the feed chamber (7), the lower end of the feed pipe (8) is connected to the interior of the vacuum induction melting furnace (1), and the discharge end of the feed pipe (8) corresponds to the high-purity alumina crucible (2).

8. The device for preparing a biodegradable alloy according to claim 7, characterized in that: The vacuum induction melting furnace (1) is provided with a pressure gauge (9) and a thermometer (10) which are in communication with the interior of the vacuum induction melting furnace (1).